Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian Handphone Merek Iphone Mahasiswa Fakultas Ekonomi Universitas Pendidikan Ganesha - Mariani, Ni Luh; Sujana, I Nyoman (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This research aims to examine the influence of price and product quality on purchasing decisions for iPhone brand cellphones among students at the Faculty of Economics, Universitas Pendidikan Ganesha. The type of research used is quantitative research. The population in this study were active students at the Faculty of Economics, Universitas Pendidikan Ganesha. The sampling technique used in this research was nonprobability sampling, or saturated sampling, so that the sample used was 96 students from the Faculty of Economics, Universitas Pendidikan Ganesha. The data collection method in this research uses the observation method and interview method as well as the questionnaire method with a Likert scale. Data processing in this research uses the SPSS version 25 for Windows program. The data analysis technique used is multiple linear regression analysis with partial (t test) and simultaneous (F test) hypothesis testing. The results of this research show that (1) price has a positive and significant effect on the decision to purchase an iPhone brand cellphone among students at the Faculty of Economics, Universitas Pendidikan Ganesha, (2) product quality has a positive and significant effect on the decision to purchase an iPhone brand cellphone among students at the Faculty of Economics, Universitas Pendidikan Ganesha, and (3) price and product quality simultaneously have a positive and significant effect on the decision to purchase an iPhone brand cellphone among students at the Faculty of Economics, Universitas Pendidikan Ganesha.